Policy Choices Can Help Keep 4G and 5G Universal Broadband Affordable - Oughton, Edward J.; Comini, Niccolo; Foster, Vivien; Hall, Jim W. (World Bank, Washington, DC, 2021)
The United Nations Broadband Commission has committed the international community to accelerate universal broadband, but the cost of meeting these objectives in the context of rapid technological change are not well understood. Using scenario analysis, this paper compares the global cost-effectiveness of different infrastructure strategies for the developing world to achieve universal 4G or 5G mobile broadband. Utilizing remote sensing and demand forecasting, least-cost network designs are developed for eight representative low- and middle-income countries (Malawi, Uganda, Kenya, Senegal, Pakistan, Albania, Peru, and Mexico), which provide the basis for aggregation to the global level. The cost of meeting UN Broadband Commission targets across the developing world is estimated at $1.6-1.7 trillion over the next decade, approximately 0.5-0.6% of annual gross domestic product for the developing world over the next decade. However, by creating a favorable regulatory environment, governments can bring down these costs by as much as three-quarters – to US$0.5 trillion (around 0.15 percent of annual gross domestic product) – and largely avoid the need for public subsidies. While 4G technology remains somewhat more cost-effective at the global scale, 5G NSA can sometimes prove less costly at the national level, particularly for countries with relatively low existing coverage of 4G technologies, and a tendency to be capacity-constrained in terms of demand. Providing that governments make judicious choices, adopting fiscal and regulatory regimes that are conducive to lowering costs, universal broadband may be within reach of most developing countries over the next decade.